Tanggungjawab Pemerintah dan Kesenjangan Sosial Dalam Pendidikan - Dianawati Lega; Hartanto (Universitas Ngudi Waluyo, 2023)
The Education Budget has been allocated at least 20%, but education issues remain an interesting study, one of which is the issue of educational equity related to inequality in Indonesia. This research is to examine the condition of education which still creates social inequality and how the Government's responsibility in it. Education is a container that facilitates what is meant by educating and developing one's potential. Gaps in social inequality are a form of inequality or unequal opportunities to access resources that occur in a society. The research method uses a normative juridical approach to examine the role of government in education Based on the 1945 Constitution Article 31 paragraph (2) and paragraph (4) concerning education and culture. The analysis shows that there are several factors that cause social inequality in education, namely; economic factors, geographic location and conditions, government constraints in equal distribution of education, lack of quality human resources, and in the future efforts must always be made to equalize education Abstrak Anggaran Pendidikan telah dialokasikan sekurang-kurangnya 20%, namun permasalahan pendidikan tetap menjadi kajian yang menarik, salah satunya pada permasalahan pemerataan pendidikan yang berkaitan dengan kesenjangan di Indonesia. Penelitian ini guna mengkaji kondisi pendidikan yang masih menimbulkan kesenjangan sosial dan bagaimana tanggungjawab Pemerintah didalamnya. Pendidikan adalah salah satu wadah yang memfasilitasi sebagaimana yang dimaksud adalah Mencerdaskan dan mengembangkan potensi dalam diri. Celah kesenjangan sosial adalah suatu bentuk ketimpangan ataupun ketidaksamaan kesempatan untuk mengakses sumber daya yang terjadi dalam suatu masyarakat. Metode Penelitian dengan mengunakan pendekatan yuridis normatif menelaah peran pemerintah dalam pendidikan Berdasarkan UUD 1945 Pasal 31 ayat (2) dan ayat (4) tentang pendidikan dan kebudayaan. Analisis menunjukkan terdapat beberapa faktor yang yang menjadi penyebab kesenjangan sosial dalam pendidikan yaitu; faktor ekonomi, letak dan kondisi geografis, kendala-kendala pemerintah dalam pemerataan pendidikan, kurangnya SDM yang berkualitas, dan dimasa depan senantiasa harus dilakukan upaya-upaya memeratakan pendidikan.